2017
DOI: 10.1177/0300060516680547
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intraoperative nausea and vomiting in caesarean delivery under regional anaesthesia

Abstract: ObjectivesThis study aimed to predict patients who have caesarean operations under regional anaesthesia and are at risk for intraoperative nausea and vomiting (IONV), for ultimately prompting anaesthetists and surgeons to take preventive measures.MethodsThis was a retrospective study on 209 patients who had caesarean section under spinal-epidural combined regional anaesthesia. The relevant medical history, such as severe nausea and vomiting in the first trimester, smoking, a history of motion sickness, and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
0
22
0
6
Order By: Relevance
“…Anesthesia-related risk factors ( Table 1 – Table 3 ) include the use of opioids, volatile agents, nitrous oxide (which increases the risk for postoperative vomiting), and high doses of neostigmine for the reversal of residual neuromuscular blockade 32 , 38 , 47 51 . General anesthesia is associated with a higher incidence of PONV compared with regional anesthesia 35 , 52 , 53 secondary to the greater requirement for opioid medication to control postoperative pain after general anesthesia in both adults and children 35 , 54 . The performance of peripheral nerve blocks 55 58 , ganglion block 59 , and wound infiltration with local anesthetic 60 has been shown to decrease the incidence of PONV.…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…Anesthesia-related risk factors ( Table 1 – Table 3 ) include the use of opioids, volatile agents, nitrous oxide (which increases the risk for postoperative vomiting), and high doses of neostigmine for the reversal of residual neuromuscular blockade 32 , 38 , 47 51 . General anesthesia is associated with a higher incidence of PONV compared with regional anesthesia 35 , 52 , 53 secondary to the greater requirement for opioid medication to control postoperative pain after general anesthesia in both adults and children 35 , 54 . The performance of peripheral nerve blocks 55 58 , ganglion block 59 , and wound infiltration with local anesthetic 60 has been shown to decrease the incidence of PONV.…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…Also a study done on 209 patients to predict the possible factors of IONV revealed that the overall incidence of IONV was 77 (36.8%) patients experienced nausea during the caesarean operation and 19 (9.1%) suffered from vomiting (10).…”
Section: Discussionmentioning
confidence: 99%
“…Increased intragastric pressure due to gravid utres, hypotension, sretching the peritoneum (exteriorization of the uterus), excessive surgical manipulation and visceral stimulation, using opioids, using uterotonic agents, visceral type of pain, and the patient's mental status play a role and place the patient at high risk for IONV (3,9,10). Hypotension associated with spinal,epidural, and spinal-epidural (combined) anaesthesia is a particularly important contributing factor for IONV (4,7,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the time to passage of first flatus and defaecation are two of the main factors that determine the postoperative patient comfort [1]. Autonomic nervous system changes that cause reduction in postoperative bowel movements are observed most commonly in caesarean section [2][3][4]. Gastrointestinal dysfunction causes accumulation of gas and secretions in the intestines resulting in nausea, vomiting, abdominal distension, pain, and ileus [5].…”
mentioning
confidence: 99%